Prevention and Treatment of Postoperative Nausea and Vomiting (PONV): A Review of Current Recommendations and Emerging Therapies - Jin Z; Gan TJ; Bergese SD (Dove Medical Press, 2020)
Zhaosheng Jin,1 Tong J Gan,1 Sergio D Bergese1,2 1Department of Anesthesiology, Stony Brook University Health Science Center, Stony Brook, NY 11794-8480, USA; 2Department of Neurological Surgery, Stony Brook University Health Science Center, Stony Brook, NY 11794-8480, USACorrespondence: Sergio D BergeseStony Brook University Health Science Center, Stony Brook, NY 11794-8480, USATel +1 631-444-2975Email Sergio.Bergese@stonybrookmedicine.eduAbstract: Postoperative nausea and vomiting is one of the most frequent adverse events after surgery and anesthesia. It is distressing for the patient and can lead to other postoperative complications. Management of PONV involves a framework of risk assessment, multimodal risk reduction, and prophylactic measures, as well as prompt rescue treatment. There has been a significant paradigm shift in the approach towards PONV prevention. There have also been several emerging therapeutic options for PONV prophylaxis and treatment. In this review, we will discuss the up-to-date PONV management guidelines and highlight novel therapeutic options which have emerged in the last few years.Keywords: antiemetics, enhanced recovery after surgery, postoperative care, postoperative nausea and vomiting